Chrysanthi Gallou, Death in Mycenaean Laconia. A Silent Place. - Dickinson, Oliver (Journal of Greek Archaeology, 2021)
This substantial study developed out of Gallou’s postdoctoral project on the Mycenaean cemeteries of Epidavros Limera, a site on the east Laconian coast that functioned as a major port in historical times. Hence, it very usefully sorts out the exceptionally complicated history of excavations at that site (generally undertaken in response to repeated tomb robbery) and in Chapter 4 publishes all the pottery in Sparta Museum from the excavations, which covers the whole chronological range from the very beginning of the Mycenaean development, in types considered transitional from Middle Helladic, to the latest-looking types of Late Helladic IIIC, often classified, as here, as Submycenaean (in the course of this Gallou sorts out certain and likely confusions involving the recording of some of the pottery).